MATH SOLVE

2 months ago

Q:
# 6° C to F: Converting 6° Celsius to Fahrenheit

Accepted Solution

A:

6° C to F: Converting 6° Celsius to Fahrenheit
Methods
Converting 6° C to F Mathematically
There is a specific formula to use when converting 6° Celsius to Fahrenheit:
F
=
C
×
9
5
+
32
F = C × \frac{9}{5} + 32
F = C × 5 9 + 32
So, to convert 6° C to F, we will want to insert the Celsius value into the equation:
F
=
6
×
9
5
+
32
F = 6 × \frac{9}{5} + 32
F = 6 × 5 9 + 32
Then we can solve the equation:
F
=
10.8
+
32
F = 10.8 + 32
F = 10.8 + 32
(If the decimal is really long, we can round to the nearest three decimal places.)
F
=
42.8
F = 42.8
F = 42.8
So:
6° Celsius = 42.8°
Fahrenheit
Try Some Other C to F Conversions
Want to be great at converting Fahrenheit to Celsius? Check out some of these other temperature conversions:
456 C to F - Converting 456 Celsius to Fahrenheit
159 C to F - Converting 159 Celsius to Fahrenheit
84 C to F - Converting 84 Celsius to Fahrenheit
462 C to F - Converting 462 Celsius to Fahrenheit
269 C to F - Converting 269 Celsius to Fahrenheit